2018
DOI: 10.21037/tcr.2018.12.07
|View full text |Cite
|
Sign up to set email alerts
|

Intensive patients’ care program ameliorates anxiety and depression, and sustained anxiety correlates with worse overall survival in renal cell carcinoma patients underwent radical nephrectomy

Abstract: Background: This study aimed to investigate the effect of an intensive patients' care program (IPCP) on anxiety, depression, and survival rate of renal cell carcinoma (RCC) patients post radical nephrectomy.Methods: This study consisted of two stages: a randomized, controlled stage (stage I) and a longterm follow-up stage (stage II). A total of 182 RCC patients who underwent radical nephrectomy were consecutively recruited and were allotted into a IPCP group (IPCP plus usual care), or a control group (only usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Two studies reported oncological outcomes in relation to anxiety and depression in patients with non-metastatic RCC. One included 1990 patients from the US [ 27 ] and one 182 patients from China [ 28 ]. When analyzing a retrospective database, Packiam et al [ 27 ] found no association of anxiety or depression with recurrence, distant metastases, overall survival (OS) or death from RCC after 10 years of follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported oncological outcomes in relation to anxiety and depression in patients with non-metastatic RCC. One included 1990 patients from the US [ 27 ] and one 182 patients from China [ 28 ]. When analyzing a retrospective database, Packiam et al [ 27 ] found no association of anxiety or depression with recurrence, distant metastases, overall survival (OS) or death from RCC after 10 years of follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing a retrospective database, Packiam et al [ 27 ] found no association of anxiety or depression with recurrence, distant metastases, overall survival (OS) or death from RCC after 10 years of follow-up. On the contrary, Song et al [ 28 ] found that patients with sustained anxiety according to the Hospital Anxiety and Depression Scale–Anxiety (HADS-A) were more likely to die from any cause with a median follow-up of 43 months. Even in the context of a randomized clinical trial (RCT), other oncological outcomes such as recurrence, metastases or cancer specific survival were not analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous study, in many depressed patients, the ineffectiveness of conventional antidepressants causes further research on the pathogenic mechanism of depression to be required (4). Some hypotheses are suggesting that depression is caused by the key role of neurotransmitters associated with other alterations, such as mitochondrial dysfunction and oxidative stress (5)(6)(7)(8)(9). Based on some evidence, depression is associated with some important cytokinesis: accompanied by activation of inflammatory pathways and reflected by an increased level of inflammatory cytokines (such as TNF-α, IL-6, IL-1β, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The following are the 4 Core Competencies: The value of IPE leading towards interprofessional collaborative practice (IPCP) in health care has been seen invaluable in achieving the Triple Aim of today's health care-improved health of the population, improved patient care experience, and improved affordability of care [6]. Indeed, IPCP has been cited as increasing outcomes in a variety of health care areas including transforming heart failure care [7], the perceptions of patients in intensive care units [8,9], and even at the end of life [10].…”
Section: Introductionmentioning
confidence: 99%